Proses Pengajaran Biokimia di Sekolah Menengah Atas Berbasis Bahan Ajar Yang Terdapat Dalam Kehidupan Sehari-hari - Bukhari Bukhari; Muhammad Muhammad; Nasruddin Nasruddin (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
A good teaching process is highly coveted by the community so that the achievement of results is maximum. Learning about biochemistry in high school must be done with teaching materials found in everyday life. Biochemical teaching material consists of carbohydrates which are divided into three groups, namely monosaccharide, disaccharide and polysarida. The second material is fat which is divided into two types when viewed from the source, namely animal fat (animal) and plant fat (vegetable). When viewed from chemical bonds also divided into two, namely saturated fat and unsaturated fat. The next material is a protein that functions to replace damaged cells, development in brain cells and as a biocatalyst.